National Road Safety Policy in Sweden as Reflected in Plans for Regional Transport Infrastructure - Värnild, Astrid; Johansson, Anna; Tillgren, Per (Scandinavian Journal of Public Administration, 2020)
In 1997 the Swedish Parliament adopted the Vision Zero road safety policy, which since 2009 is included in a consideration goal (road safety, environment, health) as one of two goals under an overall transport goal. The target of achieving Vision Zero is not specified for different authorities. Investments in infrastructure are a common way of designing a safe system. Plans for regional transport infrastructure are therefore tools to achieve the national target. The aim of the study is to analyse how Vision Zero has been applied by regional authorities as a term, a goal or a clarification in justifying measures in county plans for regional transport infrastructure in the period 2014–2025 in Sweden. Ten of twenty-one plans were included in the analysis as they selected costs for road safety measures for both state and municipal roads. The plans were analysed using directed and summative content analysis. The consideration goal is rarely in evidence. Measures are most often justified by accessibility and public transport, walking and cycling, as clarifications of the functional goal (accessibility). It is likely that the imbalance between the functional goal and the consideration goal reflects a lack of governance by the Vision Zero road safety policy.Fulfilling a national road safety target requires well-adapted sub-targets for the organizations concerned